Crisis management in a learning organization - Čendo Metzinger, Tamara; Mirenić, Ana (Crisis Management Days, 2025)
A key characteristic of a learning organization is its ability to cope with change, including, in this context, with crisis situations. Crisis situations are events characterized by factors such as suddenness, limited time for decision-making, threats to organizational goals, uncertainty, unpredictability, limited control, and impact on future operations. The timing of various types of crises cannot be fully predicted, which is why one of the essential traits of an organization is taking preventive action in the context of preparing for and reflecting on ways to respond and act during different crisis situations. This is also one of the key tasks of crisis management. As part of preventive action, crisis management must reassess and analyze past experiences, both internal and external, and apply the lessons learned during the planning and preparation phases for potential crises. Learning from crises represents organizational behavior aligned with the concept of a learning organization. Such learning contributes to organizational effectiveness, but it must become an integral part of the organization’s culture. Examining and adopting all organizational activities that proved effective in controlling and resolving a crisis, as well as changing or abandoning inadequate and ineffective procedures, is part of the learning phase whose contribution is reflected in future preventive efforts. The aim of this paper is to emphasize the importance of preventive action and systematic preparation for various types of crises, with special attention given to adopting the ideas and organizational behavior consistent with the concept of a learning organization.